2019
DOI: 10.1177/0033354918819755
|View full text |Cite|
|
Sign up to set email alerts
|

Local Decision Making for Implementing Social Distancing in Response to Outbreaks

Abstract: Objectives: Social distancing is the practice of restricting contact among persons to prevent the spread of infection. This study sought to (1) identify key features of preparedness and the primary concerns of local public health officials in deciding to implement social distancing measures and (2) determine whether any particular factor could explain the widespread variation among health departments in responses to past outbreaks. Methods:We conducted an online survey of health departments in the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 5 publications
0
22
0
Order By: Relevance
“…Social distancing can be implemented by governments at the local and state levels through one or a combination of interventions, including the closure of schools, bars, restaurants, and any social or sporting events; sick leave; work-from-home policies; splitting shifts to reduce workplace interactions; sheltering in place; and travel/trade bans (Chu et al, 2017). These interventions are critical to stopping the disease's outbreak, but quick and efficient actions by local, state, and federal governments at early stages before the epidemic gets out of control are even more critical (Katz et al, 2019). This is another source of spatial variation of the disease spread because state and local governments across the United States take different actions at different times, which could make a difference in disease outcomes.…”
mentioning
confidence: 99%
“…Social distancing can be implemented by governments at the local and state levels through one or a combination of interventions, including the closure of schools, bars, restaurants, and any social or sporting events; sick leave; work-from-home policies; splitting shifts to reduce workplace interactions; sheltering in place; and travel/trade bans (Chu et al, 2017). These interventions are critical to stopping the disease's outbreak, but quick and efficient actions by local, state, and federal governments at early stages before the epidemic gets out of control are even more critical (Katz et al, 2019). This is another source of spatial variation of the disease spread because state and local governments across the United States take different actions at different times, which could make a difference in disease outcomes.…”
mentioning
confidence: 99%
“…Danny Ibarra-Vega has developed a mathematical model with the systems dynamics methodology to evaluate the effectiveness of the quarantines or lockdowns on the reduction in community contacts for a population scale of 100,000 (Ibarra-Vega, 2020). Katz et al have sought to identify the key features of preparedness and the primary concerns of local public health officials in deciding to implement social distancing measures for the case of The U.S. (Katz et al, 2019). Jarvis et al have evaluated the effectiveness of the physical distancing measures on the transmission of COVID-19 in The U.K. (Jarvis et al, 2020).…”
mentioning
confidence: 99%
“…The search results are summarised in Figure 1. In total, 1235 citations were identi ed, of which 16 were found to be relevant [39,40,[41][42][43][44][45][46][47][48][49][50][51][52][53][54] excluded 68 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that quarantine, and school and border closure have been the most effective means of suppressing transmission [40,43]. The commonest factors associated with SDM success are support on governmental measures for social distancing and isolation by avoiding crowds, closure of public places, hand hygiene, and individuals' adherence to country-speci c mitigation measures [45,48]. Most participants felt that guidance on social distancing and isolation had been generally unclear, although some described how it had "become clearer".…”
Section: Quality Of the Studiesmentioning
confidence: 99%